Lactate dehydrogenase is a prognostic indicator for prostate cancer patients with bone metastasis - Naruse, Katsuya; Yamada, Yoshiaki; Aoki, Shigeyuki; Taki, Tomohiro; Nakamura, Kogenta; Tobiume, Motoi; Zennami, Kenji; Katsuda, Remi; Sai, Shotoku; Nishio, Yoshitaka; Inoue, Yasusuke; Noguchi, Hiroshi; et al. (Hinyokika kiyo. Acta urologica Japonica, 2007)
We analyzed clinical data to identify prognostic indicators in prostate cancer patients with bone metastasis. The subjects were 60 patients with bone metastasis out of 165 patients diagnosed with prostate cancer at our clinic over 6 years from January 1998 to December 2003. The age at the initial diagnosis was 61 to 91 (mean: 73.7 +/- 7.5) years old. The following items were considered to be possible prognostic indicators: T (type) classification, N (node) classification, Gleason score, prostate specific antigen (PSA) value before therapy, disease grade, alkaline phosphatase (ALP), lactate dehydrogenase (LDH), serum calcium (Ca), hemoglobin (Hgb), and platelet count (Plt). The 5-year overall survival rate was 45.7% in the 60 patients. Univariate analysis showed statistically significant differences in N (1), Gleason score 7 + 8/Gleason score 9 + 10, and LDH level (p = 0.0053, 0.0261, and 0.0049, respectively). Multivariate Cox proportional hazard analysis of these three items showed a statistically significant difference in LDH level and Gleason score 9 +/- 10 (p = 0.0167 and 0.0371). LDH was suggested to be an excellent prognostic indicator, because of its objectivity and convenience of measurement, in prostate cancer patients with bone metastasis.